Roman gold coin of Galba, discovered in Lombard Street and Birchin Lane, 1785 - Allen, T. (Tufts Archival Research Center, 2005)
This illustration is from the History and Antiquities of London, Westminster, Southwark and parts adjacent, Vol. 1, by Thomas Allen.